PEMIKIRAN TASAWUF AKHLÃ‚QÃŽ K.H. ASYHARI MARZUQI DAN IMPLIKASINYA DALAM KEHIDUPAN MODERN - Habibah, Aina Noor (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article explores the ideas of KH Asyhari Marzuqi?s tasawuf akhlaqi. For him, morality is categorized into two parts, namely the morality of God and morality to others. The morality of God include: first, repentance tawbat nasûhah and taqarrub, while the way of repentance and prayer can taqarrub and recitation. Second, with thanksgiving favors. And third, multiply the reading of al-Qur?ân. While the character among humans includes, first, ?al-amr bi al-ma?rûf wa al-nahy ?an al-munkar?. Second, the pilgrimage to the grave as a reminder of death. Third, convey the message. Fourth, as a kind thought khilafiyah solution. And fifth, an blessing in disguise that fear to Allah. One filter that is able to stem the current crisis is multidimensional with glorious akhlaq. Keywords: tasawuf akhlâqî, salat, zikir, dan al-amr bi al-ma?rûf.